The Art of the Surreal: Evenning sale, Tuesday 7 February 2012 at 7,00 pm immediately following the impressionist and modern art evening sale (Christie\'s Gallery, 2012)
Buku ini merupakan salah satu dari katalog galeri Christie yang dilelang pada 7 Februari 2012, tentang seni surrealisme.